Effects of Acute Hypoxia on Early Visual and Auditory Evoked Potentials - Blacker, Kara J.; McHail, Daniel G. (Frontiers in Neuroscience, 2022)
Reduced levels of environmental oxygen lead to hypoxic hypoxia and are a primary threat in tactical aviation. The visual system is particularly vulnerable to hypoxia, and its impairment can severely impact performance. The auditory system is relatively spared by hypoxia, although which stages of auditory processing are most impacted by hypoxia remains unclear. Previous work has used electroencephalography (EEG) to assess neural markers of cognitive processing for visual and auditory stimuli and found that these markers were sensitive to a normobaric hypoxic exposure. In the current study, we assessed whether early sensory evoked potentials, that precede cognitive activity, are also impaired by normobaric hypoxia. In a within-subjects design, we compared visual (P100) and auditory evoked potentials (sensory gating for the P50, N100, and P200) in 34 healthy adults during normoxic (21% O2) and two separate hypoxic (9.7% O2) exposures. Self-reported symptoms of hypoxia were also assessed using the Hypoxia Symptom Questionnaire (HSQ). We found that P100 mean amplitude was not reduced under hypoxic compared to normoxic conditions, suggesting no statistically significant impairment of early visual processing. The sensory gating ratio for auditory stimuli was intact for paired responses of the P50 and N100. However, the P200 sensory gating ratio was attenuated under hypoxic compared to normoxic conditions, suggesting disruption of the auditory system specific to the level of allocating attention that follows basic auditory processing. Exploratory analyses of HSQ scores identified a robust effect of hypoxia. However, consistency of symptoms reported between the two hypoxia exposures exhibited high intra-individual variability, which may have implications for the theory that individuals have a consistent hypoxia signature or reliable constellation of responses to hypoxia. These findings suggest that early sensory processing is not impaired during hypoxia, but for the auditory system there is impairment at the level of attentional processing. Given the previous findings of impaired visual performance under hypoxia, these results suggest that this impairment does not stem from early visual processing deficits in visual cortex. Together these findings help focus the search on when and where hypoxia-induced deficits occur and may guide the development of countermeasures for hypoxia in tactical aviation.